2022
DOI: 10.1177/03635465221131295
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Risk Factors for Posterior Cruciate Ligament Tear and Tibial Avulsion Injuries of the Tibial Plateau and Femoral Condyle

Abstract: Background: Identification of morphological risk factors associated with the knee that threaten ligaments is important for understanding injury mechanisms and prevention. However, the morphological risk factors for posterior cruciate ligament (PCL) lesions are not clearly understood. Purpose: To investigate whether the medial tibial depth (MTD), medial and lateral posterior tibial slope, asymmetry of the medial and lateral slopes, radius of the sagittal plane medial femoral condyle, coronal tibial slope, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…One study found that the 10‐year graft survival rates were 68.4% for patients with an MTS of ≤5.6° versus 92.6% for patients with an MTS of >5.6° ( p = 0.029) [26]. Four studies reported a mean MTS of 4.3 (range: 3.0–7.0) degrees in the PCL rupture or graft failure group and 6.5 (range: 5.0–9.2) degrees in the control group [17, 18, 22, 25]. All four studies found that patients with PCL injury had significantly flatter MTS than controls ( p < 0.001, p = 0.014, p = 0.023, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study found that the 10‐year graft survival rates were 68.4% for patients with an MTS of ≤5.6° versus 92.6% for patients with an MTS of >5.6° ( p = 0.029) [26]. Four studies reported a mean MTS of 4.3 (range: 3.0–7.0) degrees in the PCL rupture or graft failure group and 6.5 (range: 5.0–9.2) degrees in the control group [17, 18, 22, 25]. All four studies found that patients with PCL injury had significantly flatter MTS than controls ( p < 0.001, p = 0.014, p = 0.023, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…One study reported an AUC of 0.765 and an MTS cutoff of under 3.9° being predictive of PCL rupture, with a sensitivity and specificity of 76.1% and 73.9%, respectively [22]. Another study reported an AUC of 0.690 and an MTS cutoff of under 3.93° being predictive of PCL rupture in males, with a sensitivity and specificity of 68.4% and 81.4%, respectively ( p < 0.001) [17]. In one study, a simple logistic regression analysis of MTS was found to be predictive of PCL rupture with a significant OR of 1.19 (95% CI, 1.04–1.37, p = 0.011); however, this relationship did not remain significant after multivariate analysis with an adjusted OR of 1.20 (95% CI, 0.95–1.52, n.s.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations